2019
DOI: 10.1038/s41467-019-13708-y
|View full text |Cite
|
Sign up to set email alerts
|

Uterine adenomyosis is an oligoclonal disorder associated with KRAS mutations

Abstract: Uterine adenomyosis is a benign disorder that often co-occurs with endometriosis and/or leiomyoma, and impairs quality of life. The genomic features of adenomyosis are unknown. Here we apply next-generation sequencing to adenomyosis (70 individuals and 192 multi-regional samples), as well as co-occurring leiomyoma and endometriosis, and find recurring KRAS mutations in 26/70 (37.1%) of adenomyosis cases. Multi-regional sequencing reveals oligoclonality in adenomyosis, with some mutations also detected in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
134
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 37 publications
5
134
0
Order By: Relevance
“…A recent study involving genomic analysis of adenomyosis indicated high variant allele frequencies of KRAS hotspot mutations in the microdissected epithelial cells of adenomyotic tissue, which suggested that adenomyosis may arise from the ectopic proliferation of mutated epithelial cell clones (Inoue et al, 2019). Furthermore, they found identical KRAS mutations in adenomyotic and histologically normal endometrium adjacent to adenomyotic lesions and argued that "KRAS-mutated adenomyotic clones originate from normal endometrium" (Inoue et al, 2019). Our findings of the 3D morphology of adenomyosis support this hypothesis from a histological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving genomic analysis of adenomyosis indicated high variant allele frequencies of KRAS hotspot mutations in the microdissected epithelial cells of adenomyotic tissue, which suggested that adenomyosis may arise from the ectopic proliferation of mutated epithelial cell clones (Inoue et al, 2019). Furthermore, they found identical KRAS mutations in adenomyotic and histologically normal endometrium adjacent to adenomyotic lesions and argued that "KRAS-mutated adenomyotic clones originate from normal endometrium" (Inoue et al, 2019). Our findings of the 3D morphology of adenomyosis support this hypothesis from a histological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in next-generation sequencing (NGS) have allowed deep sequencing of human cancers, precancerous epithelium, and lesions previously considered to be non-neoplastic, such as endometriosis, 1,2 uterine adenomyosis, 3 and brain arteriovenous malformations. 4 NGS detects oncogenic mutations even in small cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…External physical/mechanical factors such as caesarean section can induce reactions that trigger genomic alterations in NE. Notably, recurrent mutations affecting KRAS and PIK3CA have been reported in NE [3][4][5][6] . Increased age, high body mass index and parity may be associated with a burden of mutations in NE 4,5 .…”
mentioning
confidence: 99%
“…Endometrium-like epithelial cells that ectopically proliferate in normal myometrium (NM). Mutation of KRAS and/or PIK3CA in NE is the earliest events in the molecular pathogenesis of adenomyosis 3 . It has been shown that parity, spontaneous abortion and smoking could be risk factors for adenomyosis 7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation